Pengaruh content marketing dan electronic word of mouth (E-WoM) terhadap purchase decision produk Skin1004 yang dimediasi oleh fear of missing out (FoMO) (studi kasus pada Gen Z di Kota Palu) - Fitrianingsih, Ananda; Bachri, Syamsul; Muzakir; Farid (Universitas Widya Mataram, 2025)
In the current digital era, digital marketing strategies are increasingly used by various companies, including Skin1004, ranging from content marketing creation to the utilization of E-WoM. This has led to the emergence of the FoMO phenomenon, which has now become an important factor influencing purchase decisions, especially among Gen Z. This study aims to analyze and determine the effect of content marketing and electronic word of mouth on the purchase decision of Skin1004 products, mediated by fear of missing out (FoMO) among Gen Z in Palu City. The research method used is quantitative with Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS). The sample was taken using purposive sampling with 150 respondents. The results of the study show that the content marketing variable has a positive and significant effect on fear of missing out and purchase decision, the electronic word of mouth variable has a positive and significant effect on fear of missing out and purchase decision, the fear of missing out variable has a positive and significant effect on purchase decision, and the fear of missing out variable can mediate the effect of content marketing on purchase decision and the effect of electronic word of mouth on purchase decision.